Socioeconomic Impact of COVID-19 on Sudanese Households - World Bank (World Bank, Washington, DC, 2021)
Sudan, like the rest of the world, has been experiencing the unprecedented social and economic impact of the Coronavirus (COVID-19) pandemic. The Sudanese authorities attempted to act quickly in the face of the spreading virus. In March 2020 the government established a high-level emergency committee to oversee the operations to deal with the Coronavirus (COVID-19) pandemic. The government imposed closure of schools, airports, ports, and land crossings, banned travel between states, and prohibited mass gatherings. A partial lockdown was imposed in Khartoum State in mid-March 2020. Restrictions on movement are expected to make the economic situation worse, with commodity prices soaring across the country. The rapid spread of Coronavirus (COVID-19) in Sudan and the government’s containment measures could negatively affect household welfare including loss of employment and income, decreased access to basic commodities and services, and food security. The objective of the Sudan high frequency survey on Coronavirus (COVID-19) is to quickly collect household (and firm-level) information, using phones, to monitor the crisis and assess the dynamics of the impacts of Coronavirus (COVID-19) on households and micro, small and medium enterprises [MSMEs] in Sudan. The survey will help inform dialogue and mitigation measures. The survey focuses on the socioeconomic impacts of Coronavirus (COVID-19) on households in urban and rural areas and provides near real-time data, supporting an evidence-based response to the crisis.